2011
DOI: 10.1037/a0022590
|View full text |Cite
|
Sign up to set email alerts
|

The role of awakening cortisol and psychological distress in diurnal variations in affect: A day reconstruction study.

Abstract: People often feel unhappy in the morning but better later in the day, and this pattern may be amplified in the distressed. Past work suggests that one function of cortisol is to energize people in the mornings. In a study of 174 students we tested to see if daily affect patterns, psychological distress, and awakening cortisol levels were interlinked. Affect levels were assessed using the Day Reconstruction Method (Kahneman, Krueger, Schkade, Schwarz, & Stone, 2004) and psychological distress was measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
3
10
0
Order By: Relevance
“…Instead, our findings replicate the more pronounced quadratic MDD PA pattern found in Peeters et al (2006). The finding that 'morning-worse' mood in MDD is expressed via PA lows rather than NA highs is in keeping with recent research, which also found the 'morning-worse' depression pattern to be much more pronounced in PA than NA (Daly et al, 2011). Again, this emphasizes the prevalence and importance of PA dynamics in MDD.…”
Section: 2 Diurnal Time-trends In Positive Affect Tiredness Suisupporting
confidence: 91%
See 2 more Smart Citations
“…Instead, our findings replicate the more pronounced quadratic MDD PA pattern found in Peeters et al (2006). The finding that 'morning-worse' mood in MDD is expressed via PA lows rather than NA highs is in keeping with recent research, which also found the 'morning-worse' depression pattern to be much more pronounced in PA than NA (Daly et al, 2011). Again, this emphasizes the prevalence and importance of PA dynamics in MDD.…”
Section: 2 Diurnal Time-trends In Positive Affect Tiredness Suisupporting
confidence: 91%
“…MDD participants, however, showed a significantly steeper slope in PA over the day, with relatively lower morning and higher evening levels. These findings are similar to those of Daly et al (2011), where individuals with high levels of psychological distress had a more pronounced diurnal affective rhythm than those with low distress levels, characterized by much lower morning PA and somewhat higher morning NA. In contrast, Murray (2007) found a less distinct diurnal quadratic rhythm in PA in individuals with high depression levels compared to those with low depression levels.…”
Section: Diurnal Time-trends In Affect Relatively Little Research Exsupporting
confidence: 84%
See 1 more Smart Citation
“…According to some previous studies, high cortisol values in the morning have been associated with distress and anticipation of a busy and potentially stressful day (Kunz-Ebrecht et al 2008;Thorn et al 2011). It has also been suggested that higher than average morning cortisol values predict an increasing pattern of negative affect throughout the day (Daly et al 2011). On the other hand, the absence of a morning effect has been linked to long-term overload of the system regulating stress and to increased developmental risk (Gunnar 2001;Chida and Steptoe 2009).…”
Section: European Early Childhood Education Research Journalmentioning
confidence: 97%
“…A series of multilevel analyses was conducted to assess bivariate relationships between the Dark Triad traits and momentary affect with the number of the episode (a level-1 predictor) as a control variable (within-person: y ij = β 0j + β ij (EPISODE) + r ij ) and each Dark Triad trait as a level-2 predictor (between-person: β 0j = γ 00 + γ 01 (Trait) + u 0j , β 1j = γ 10 + u 1j ). The number of the episode was chosen as a control variable because past research using the DRM showed that time of a day is an important predictor of positive and negative affect: across the day, positive affect increases and negative affect decreases [120,121]. Table 2 contains a summary of the analyses for momentary PA, momentary NA and affect balance.…”
Section: Preliminary Analysesmentioning
confidence: 99%